Impact of Flood on Rice Business Income in Ibul Besar I Village Pemulutan District Ogan Ilir Regency - Hakita Karina, Fellicia; Husin, Laila (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2022)
The flood disaster that occurred became a problem in Ibul Besar Village I, Pemulutan District, Ogan Ilir Regency. With this flood, it can have an influence on cropping patterns and agricultural production costs so that it affects agricultural yields and the income of rice farmers whose rice farms are affected by flooding when there are plants. This study aims to (1) identify the conditions, causes, and problems of flooding experienced by rice farmers in Ibul Besar I Village, (2) Analyze the amount of income of rice farmers before and during the flood in Ibul Besar I Village, (3) Analyze the impact of flooding on the income of rice farmers in Ibul Besar Village I. This research was carried out in Ibul Besar I Village. The location of this research was determined purposively by considering that Ibul Besar I Village is an area experiencing flooding. The time of data collection and collection in the field was carried out in July 2022. The research method used was a survey method and the sampling method used in this study was simple random sampling with 30 samples considered homogeneous with the criteria of rice farmers whose land was flooded. The results showed that (1) Flood conditions in Ibul Besar I Village occurred 2 times in one year, namely the first flood in the month 2 times in one year. The first flood occurred in April with a height of 50 cm. The second flood occurred in November with a height of 60-100 cm. Floods that occur are caused by the influence of tidal water in the river, high rainfall, and malfunctioning of the floodgates. The problems faced by farmers are crop failure, delays in cropping and harvesting schedules and the occurrence of crop failure, (2) The average income received by farmers before the flood was Rp. 11,526,466.67/lg/year while the average income of farmers after the flood amounting to Rp9,886,800/lg/year. The magnitude of the difference in income between rice farmers before and after the flood was Rp. 1,639,666.67/lg/year, (3) The impact of flooding on farmers income in Ibul Besar I Village, seen from the five indicators, it was found that 68% of the livelihood indicators had an effect on their livelihoods and 32% had no effect on their livelihoods. Farming indicators 38% have an effect on farming and 62% have no effect on farming. The 39% productivity indicator has an effect on productivity and 61% has no effect on productivity. The expenditure indicator 73% has an effect on the expenditure and 27% has no effect on the expenditure. The welfare indicator 67% has an effect on their welfare and 33% has no effect on their welfare.